Motivasi Belajar Siswa Madrasah Tsanawiyah berdasarkan Kompetensi Guru Bahasa Arab - Arlin Nuhia; Moh Zulkifli Paputungan; Chaterina Puteri Doni; Fira S. Damulawan (Al-Kilmah: Jurnal Pendidikan Bahasa Arab dan Humaniora, 2023)
This study examines the influence of Arabic teachers' professional competence on students' learning motivation at Madrasah Tsanawiyah Cokroaminoto Duminanga. The background of this research highlights the critical role of teachers in fostering student motivation, particularly in the context of learning Arabic, which is not only a communication tool but also a medium for religious education. The primary objective is to assess how the professional competence of Arabic language teachers affects students' motivation to learn. Utilizing a quantitative research method, data were collected through structured questionnaires distributed to 20 students. The reliability of the instruments was tested using Cronbach's Alpha, while validity was confirmed through product-moment correlation. Data analysis was performed using simple regression to determine the impact of the independent variable (teacher competence) on the dependent variable (student motivation). The results reveal a significant positive correlation between the teachers' professional competence and the students' motivation, suggesting that enhancing teacher quality can directly improve student engagement and learning outcomes. This study underscores the importance of continuous professional development for teachers to sustain student motivation, with implications for educational policy and teacher training programs.